Magnetic ternary composite SERS (Surface Enhanced Raman Scattering) substrate capable of being degraded and recycled through photocatalysis as well as preparation method and application of SERS substrate

By preparing magnetic ternary composite photocatalytic degradation and recycling SERS substrates, using the modification and incubation of materials such as Co/C, Ag NPs and g-C3N4, the existing SERS substrates are solved, and the cost of use and limitations are achieved is efficient visible photocatalytic degradation and multiple reuses are reduced, and the cost of use is improved and the recycling ability of the material is improved.

CN119534423APending Publication Date: 2025-02-28XINJIANG NORMAL UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411715856.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing SERS substrates have problems such as high cost of use, high limitations, complex preparation process, long time consumption and serious chemical pollution, and it is difficult to achieve long-term storage and recycling.

Method used

The preparation method of magnetic ternary composite photocatalytic degradation and recovery of SERS substrates is adopted. By modifying and incubating materials such as Co/C, Ag NPs and g-C3N4, a composite structure of Co/C/Ag/g-C3N4 or Co/C/g-C3N4/Ag is formed to realize visible photocatalytic degradation and SERS detection.

Benefits of technology

The efficient visible photocatalytic degradation and multiple reuse of magnetic ternary composite SERS substrates are achieved, which reduces the cost of use, improves the recycling capacity of materials, and reduces chemical pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119534423A_ABST
    Figure CN119534423A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of surface enhanced Raman scattering (SERS) substrates, and provides a magnetic ternary composite SERS substrate capable of being degraded and recycled through photocatalysis as well as a preparation method and application of the SERS substrate. The method comprises the following steps: carrying out modification treatment on Co / C or Co / C / g-C3N4 by using (3-aminopropyl) triethoxysilane, so as to obtain modified Co / C or modified Co / C / g-C3N4; mixing the modified Co / C with the Ag NPs solution to obtain Co / C / Ag; co / C / Ag and g-C3N4 are mixed for incubation, Co / C / Ag / g-C3N4 is obtained, or modified Co / C / g-C3N4 and an Ag NPs solution are mixed, and Co / C / g-C3N4 / Ag is obtained. The magnetic ternary composite SERS substrate capable of being degraded and recycled through photocatalysis is designed and prepared, and very excellent enhanced Raman performance and visible light catalysis effect are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface enhanced Raman scattering substrates, and in particular to a magnetic ternary composite photocatalytically degradable and recyclable SERS substrate, and a preparation method and application thereof. Background Art

[0002] Surface enhanced Raman scattering (SERS) can be used to quickly measure pesticide and veterinary drug residues. The SERS substrates reported so far have good stability and enhancement effects, but they are basically disposable, and due to the spontaneous aggregation of plasma nanoparticles, they cannot be stored for a long time. This leads to high cost and limitations of SERS substrates. In addition, the SERS substrates currently used have the defects of complex preparation process, long time consumption, many reagents used, and serious chemical pollution.

[0003] In the past two years, researchers have turned their attention to recyclable SERS substrates. The principles of recycling can be divided into the following categories: 1. Washable recyclable substrates; 2. Catalytic decomposition recyclable substrates. Among them, photocatalysis combined with SERS detection has been proven to be a promising green treatment method. Photocatalytic activity can make the substrate self-cleaning and reusable. Therefore, the research on various photocatalysts has received widespread attention, mainly including traditional metal oxides (TiO, ZnO) and new two-dimensional materials (black phosphorus, boron nanosheets, two-dimensional antimonene-based materials and MXene). However, metal oxides have large band gaps, require ultraviolet light irradiation, and their photocatalytic performance is barely satisfactory; the development of high-quality and high-yield new two-dimensional materials is technically demanding. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems existing in the prior art and to provide a magnetic ternary composite photocatalytically degradable and recyclable SERS substrate and a preparation method and application thereof.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a magnetic ternary composite photocatalytically degradable and recyclable SERS substrate, comprising the following steps:

[0007] (1) Co / C, (3-aminopropyl)triethoxysilane and toluene are mixed and modified to obtain modified Co / C;

[0008] (2) mixing the modified Co / C and Ag NPs solutions to obtain Co / C / Ag;

[0009] (3) mixing Co / C / Ag and g-C3N4 and incubating them to obtain the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate;

[0010] Alternatively, (a) Co / C / g-C3N4, (3-aminopropyl)triethoxysilane and toluene are mixed and modified to obtain modified Co / C / g-C3N4;

[0011] (b) The modified Co / C / g-C3N4 and AgNPs solution are mixed to obtain the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate.

[0012] Preferably, the preparation method of Co / C in step (1) comprises the following steps:

[0013] Cobalt nitrate, 2-methylimidazole and methanol are mixed and aged to obtain a zeolite imidazole framework; the zeolite imidazole framework is subjected to a first calcination and a second calcination in sequence under a protective atmosphere to obtain Co / C;

[0014] The preparation method of Co / C / g-C3N4 in step (a) comprises the following steps:

[0015] (I) melamine is subjected to a first calcination and a second calcination in sequence, and then a sample obtained by the second calcination is mixed with methanol and subjected to ultrasonic treatment to obtain g-C3N4;

[0016] (II) Cobalt nitrate, 2-methylimidazole, methanol and g-C3N4 are mixed and aged to obtain a composite framework; under a protective atmosphere, the composite framework is subjected to a first calcination and a second calcination in sequence to obtain Co / C / g-C3N4.

[0017] Preferably, the mass volume ratio of Co / C, (3-aminopropyl)triethoxysilane and toluene in step (1) is 0.1-1 g: 1-2 mL: 35-60 mL;

[0018] The mass volume ratio of Co / C / g-C3N4, (3-aminopropyl)triethoxysilane and toluene in step (a) is 0.1-1 g: 1-2 mL: 35-60 mL.

[0019] Preferably, the temperature of the modification treatment in step (1) and the temperature of the modification treatment in step (a) are independently 100 to 120° C., and the time of the modification treatment in step (1) and the time of the modification treatment in step (a) are independently 22 to 26 hours.

[0020] Preferably, the preparation method of the Ag NPs in step (2) and the Ag NPs in step (b) comprises the following steps:

[0021] Silver nitrate, water, and sodium citrate solution were mixed and reacted, and then a sample obtained by the reaction was mixed with ethanol to obtain Ag NPs.

[0022] Preferably, the solvent of the Ag NPs solution in step (2) and the Ag NPs solution in step (b) is water, and the mass fraction of the Ag NPs solution in step (2) and the mass fraction of the Ag NPs solution in step (b) are independently 0.01 to 0.1%;

[0023] The mass volume ratio of the modified Co / C and Ag NPs solution in step (2) is 25-35 mg: 180-220 mL; the mass volume ratio of the modified Co / C / g-C3N4 and Ag NPs solution in step (b) is 25-35 mg: 180-220 mL;

[0024] The mixing temperature in step (2) and the mixing temperature in step (b) are independently 20 to 30° C., and the mixing time in step (2) and the mixing time in step (b) are independently 25 to 35 minutes.

[0025] Preferably, the preparation method of g-C3N4 in step (3) comprises the following steps:

[0026] Melamine is subjected to a first calcination and a second calcination in sequence, and then the sample obtained by the second calcination is mixed with methanol and subjected to ultrasonic treatment to obtain g-C3N4.

[0027] Preferably, the mass ratio of Co / C / Ag and g-C3N4 in step (3) is 25-35 mg: 25-35 mg;

[0028] The incubation temperature in step (3) is 20-30° C., and the incubation time is 25-35 min.

[0029] The present invention also provides a magnetic ternary composite photocatalytically degradable and recyclable SERS substrate prepared by the preparation method of the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate.

[0030] The present invention also provides application of the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate in surface enhanced Raman scattering.

[0031] The beneficial effects of the present invention are:

[0032] The invention provides a preparation method of a magnetic ternary composite photocatalytically degradable and recyclable SERS substrate, comprising the following steps: mixing Co / C, (3-aminopropyl) triethoxysilane and toluene, performing a modification treatment to obtain modified Co / C; mixing the modified Co / C and an Ag NPs solution to obtain Co / C / Ag; mixing Co / C / Ag and g-C3N4, performing incubation to obtain a magnetic ternary composite photocatalytically degradable and recyclable SERS substrate (Co / C / Ag / g-C3N4); or, mixing Co / C / g-C3N4, (3-aminopropyl) triethoxysilane and toluene, performing a modification treatment to obtain modified Co / C / g-C3N4; mixing the modified Co / C / g-C3N4 and an AgNPs solution to obtain a magnetic ternary composite photocatalytically degradable and recyclable SERS substrate (Co / C / g-C3N4 / Ag). The present invention designs and prepares a Co / C / Ag / g-C3N4 substrate and a Co / C / g-C3N4 / Ag substrate. The three components are combined and synergistic to achieve a very excellent visible light catalytic effect.

[0033] Specifically, Co / C has the following functions: 1. It makes the magnetic ternary composite photocatalytic degradation and recycling SERS substrate magnetic, which is convenient for separation from the target substance for reuse; 2. The highly dispersed Co intermediate and the graphene carbon on the surface can promote electron transfer and increase the diffusion rate of electrons, thereby preventing the recombination of electrons and holes in g-C3N4; 3. The porosity and large specific surface area give the material excellent organic molecule enrichment ability, which can enrich the target substance near AgNPs to produce a strong SERS signal;

[0034] g-C3N4 is a two-dimensional graphene analog material with high visible light absorption, good chemical stability and thermal stability, and a simple preparation method. It is an effective visible light photocatalyst; g-C3N4 has a large number of nitrogen active sites on the surface, which can adsorb and fix noble metal nanoparticles and form hot spots. Ag NPs show high dispersibility. AgNPs and g-C3N4 are conducive to the formation of SERS detection hot spots and photocatalytic degradation active sites. Ag NPs can not only provide surface plasmons that enhance Raman scattering, but also store photoelectrons as an electron pool. At the same time, they can also transfer the photoelectrons generated by g-C3N4 to Co / C to separate electrons and electron holes, thereby improving the separation efficiency of pure g-C3N4 electron-hole pairs. In addition, g-C3N4 can also efficiently enrich target molecules near AgNPs, making the composite substrate have stronger SERS performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a SEM characterization image of the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate in Example 1;

[0036] Figure 2 This is a TEM characterization image of the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate in Example 1;

[0037] Figure 3 The SERS spectrum (Raman shift, Raman intensity) of the magnetic ternary composite photocatalytic degradation and recovery SERS substrate to the malachite green solution in Example 1;

[0038] Figure 4 The Raman spectra and linear relationship diagrams (Raman shift, Raman intensity) under different malachite green concentrations are shown in Figure 2. Figure 4 In the figure, A is the Raman spectra of different malachite green concentrations, and B is the corresponding 1613cm -1 Linear plot of intensity at wavenumber;

[0039] Figure 5 This is a schematic diagram of the recovery performance of the magnetic ternary composite photocatalytic degradation and recovery SERS substrate in Example 1 (Cycle Number—cycle number, Intensity—intensity). DETAILED DESCRIPTION

[0040] The present invention provides a method for preparing a magnetic ternary composite photocatalytically degradable and recyclable SERS substrate, comprising the following steps:

[0041] (1) Co / C, (3-aminopropyl)triethoxysilane and toluene are mixed and modified to obtain modified Co / C;

[0042] (2) mixing the modified Co / C and Ag NPs solutions to obtain Co / C / Ag;

[0043] (3) mixing Co / C / Ag and g-C3N4 and incubating them to obtain the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate;

[0044] Alternatively, (a) Co / C / g-C3N4, (3-aminopropyl)triethoxysilane and toluene are mixed and modified to obtain modified Co / C / g-C3N4;

[0045] (b) The modified Co / C / g-C3N4 and AgNPs solution are mixed to obtain the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate.

[0046] In the present invention, the preparation method of Co / C in step (1) preferably comprises the following steps:

[0047] Cobalt nitrate, 2-methylimidazole and methanol are mixed and aged to obtain a zeolite imidazole framework; the zeolite imidazole framework is subjected to a first calcination and a second calcination in sequence under a protective atmosphere to obtain Co / C.

[0048] In the present invention, cobalt nitrate is preferably cobalt nitrate hexahydrate; the mixing of cobalt nitrate, 2-methylimidazole and methanol preferably comprises the following steps: mixing cobalt nitrate hexahydrate and the first part of methanol to obtain solution a; mixing 2-methylimidazole and the remaining methanol to obtain solution b; rapidly pouring solution b into solution a and stirring to complete the mixing of cobalt nitrate, 2-methylimidazole and methanol; the molar volume ratio of cobalt nitrate hexahydrate, the first part of methanol, 2-methylimidazole and the remaining methanol is preferably 0.01-0.02 mol:350-450 mL: 0.06-0.07 mol: 350-450 mL, more preferably 0.012-0.018 mol: 370-430 mL: 0.062-0.068 mol: 370-430 mL, more preferably 0.014-0.015 mol: 390-400 mL: 0.064-0.065 mol: 390-400 mL; the stirring time is preferably 5-15 min, more preferably 7-13 min, more preferably 10-11 min.

[0049] In the present invention, the aging treatment temperature is preferably 20-30°C, more preferably 22-28°C, more preferably 25-26°C; the aging treatment time is preferably 22-26h, more preferably 23-25h, more preferably 23.5-24h.

[0050] In the present invention, after the aging treatment is completed, centrifugation is performed to obtain a purple solid; the purple solid is washed with methanol, and the number of washings is preferably ≥1 times, more preferably ≥2 times, and more preferably ≥3 times; after washing, drying is performed to obtain a zeolite imidazole framework (ZIF-67); the drying temperature is preferably 50-70°C, more preferably 55-65°C, and more preferably 60-62°C; the drying time is preferably 22-26h, more preferably 23-25h, and more preferably 23.5-24h.

[0051] In the present invention, the protective atmosphere is preferably a nitrogen atmosphere; the temperature of the first calcination is preferably 140-160°C, more preferably 145-155°C, and more preferably 150-152°C; the holding time of the first calcination is preferably 1-3h, more preferably 1.5-2.5h, and more preferably 1.8-2h; the temperature of the second calcination is preferably 780-820°C, more preferably 790-810°C, and more preferably 800-805°C; the holding time of the second calcination is preferably 5-7h, more preferably 5.5-6.5h, and more preferably 5.8-6h; the heating rate from the temperature of the first calcination to the temperature of the second calcination is preferably 3-7°C / min, more preferably 4-6°C / min, and more preferably 5-5.5°C / min.

[0052] In the present invention, after the second calcination is completed, the mixture is naturally cooled to room temperature to obtain Co / C.

[0053] In the present invention, the preparation method of Co / C / g-C3N4 in step (a) preferably comprises the following steps:

[0054] (I) melamine is subjected to a first calcination and a second calcination in sequence, and then a sample obtained by the second calcination is mixed with methanol and subjected to ultrasonic treatment to obtain g-C3N4;

[0055] (II) Cobalt nitrate, 2-methylimidazole, methanol and g-C3N4 are mixed and aged to obtain a composite framework; under a protective atmosphere, the composite framework is subjected to a first calcination and a second calcination in sequence to obtain Co / C / g-C3N4.

[0056] In the present invention, the temperature of the first calcination in step (I) is preferably 500-600°C, more preferably 520-580°C, and more preferably 550-560°C; the time of the first calcination is preferably 3-5h, more preferably 3.5-4.5h, and more preferably 3.9-4h; the temperature of the second calcination in step (I) is preferably 500-600°C, more preferably 520-580°C, and more preferably 550-560°C; the time of the second calcination is preferably 1-3h, more preferably 1.5-2.5h, and more preferably 1.9-2h.

[0057] In the present invention, in step (I), the mass volume ratio of the sample obtained by the second calcination to methanol is preferably 0.05-0.15 g: 3-7 mL, more preferably 0.07-0.13 g: 4-6 mL, and more preferably 0.1 g: 5 mL; the time of ultrasonic treatment is preferably 100-140 min, more preferably 110-130 min, and more preferably 120-125 min.

[0058] In the present invention, in step (II), the cobalt nitrate is preferably cobalt nitrate hexahydrate; the mixing of cobalt nitrate, 2-methylimidazole, methanol and g-C3N4 preferably comprises the following steps: mixing cobalt nitrate hexahydrate and the first part of methanol to obtain solution a; mixing 2-methylimidazole and the remaining methanol to obtain solution b; adding g-C3N4 to solution a, performing a first stirring, and then quickly pouring solution b into solution a containing g-C3N4, performing a second stirring, and completing mixing; the molar volume ratio of cobalt nitrate hexahydrate, the first part of methanol, 2-methylimidazole and the remaining methanol is preferably 0.01-0.02 mol: 350-450 mL: 0.06-0.07 mol: 350-450 mL, and more preferably 0.012-0. 0.018mol:370~430mL:0.062~0.068mol:370~430mL, more preferably 0.014~0.015mol:390~400mL:0.064~0.065mol:390~400mL; the mass molar ratio of g-C3N4 and cobalt nitrate hexahydrate is preferably 0.5~1.5g:0.01~0.02mol, more preferably 0.7~1.3g:0.012~0.018mol, more preferably 0.9~1.0g:0.014~0.015mol; the first stirring time and the second stirring time are independently preferably 5~15min, more preferably 7~13min, more preferably 10~11min.

[0059] In the present invention, in step (II), the temperature of the aging treatment is preferably 20-30°C, more preferably 22-28°C, and more preferably 25-26°C; the time of the aging treatment is preferably 22-26h, more preferably 23-25h, and more preferably 23.5-24h.

[0060] In the present invention, in step (II), after the aging treatment is completed, centrifugation is performed to obtain a purple solid; the purple solid is washed with methanol, and the number of washings is preferably ≥1 times, more preferably ≥2 times, and more preferably ≥3 times; after washing, drying is performed to obtain a composite skeleton (ZIF-67 / g-C3N4); the drying temperature is preferably 50-70°C, more preferably 55-65°C, and more preferably 60-62°C; the drying time is preferably 22-26h, more preferably 23-25h, and more preferably 23.5-24h.

[0061] In the present invention, in step (II), the protective atmosphere is preferably a nitrogen atmosphere; the temperature of the first calcination is preferably 140-160°C, more preferably 145-155°C, and more preferably 150-152°C; the holding time of the first calcination is preferably 1-3h, more preferably 1.5-2.5h, and more preferably 1.8-2h; the temperature of the second calcination is preferably 450-550°C, more preferably 470-530°C, and more preferably 500-510°C; the holding time of the second calcination is preferably 5-7h, more preferably 5.5-6.5h, and more preferably 5.8-6h; the heating rate from the temperature of the first calcination to the temperature of the second calcination is preferably 3-7°C / min, more preferably 4-6°C / min, and more preferably 5-5.5°C / min.

[0062] In the present invention, in step (II), after the second calcination is completed, it is naturally cooled to room temperature to obtain Co / C / g-C3N4.

[0063] In the present invention, before the Co / C in step (1) is mixed with (3-aminopropyl)triethoxysilane and toluene, and before the Co / C / g-C3N4 in step (a) is mixed with (3-aminopropyl)triethoxysilane and toluene, the Co / C and Co / C / g-C3N4 are preferably vacuum dried first; the vacuum drying temperature of Co / C and the vacuum drying temperature of Co / C / g-C3N4 are independently preferably 50-70°C, further preferably 55-65°C, and more preferably 60-62°C; the vacuum drying time of Co / C and the vacuum drying time of Co / C / g-C3N4 are independently preferably 4-6h, further preferably 4.5-5.5h, and more preferably 4.7-5h.

[0064] In the present invention, the mass volume ratio of Co / C, (3-aminopropyl)triethoxysilane and toluene in step (1) is preferably 0.1-1 g: 1-2 mL: 35-60 mL, more preferably 0.3-0.8 g: 1.2-1.8 mL: 40-55 mL, and more preferably 0.5-0.6 g: 1.5-1.6 mL: 45-50 mL.

[0065] In the present invention, the mass volume ratio of Co / C / g-C3N4, (3-aminopropyl)triethoxysilane and toluene in step (a) is preferably 0.1-1 g: 1-2 mL: 35-60 mL, more preferably 0.3-0.8 g: 1.2-1.8 mL: 40-55 mL, and more preferably 0.5-0.6 g: 1.5-1.6 mL: 45-50 mL.

[0066] In the present invention, the temperature of the modification treatment in step (1) and the temperature of the modification treatment in step (a) are independently preferably 100-120°C, more preferably 105-115°C, and more preferably 110-112°C; the time of the modification treatment in step (1) and the time of the modification treatment in step (a) are independently preferably 22-26h, more preferably 23-25h, and more preferably 23.5-24h.

[0067] In the present invention, after the modification treatment in step (1) or step (a) is completed, the obtained sample is washed with ethanol, and the number of washings is preferably ≥1 time, more preferably ≥2 times, and more preferably ≥3 times; after washing, vacuum drying is carried out, and the vacuum drying temperature is preferably 50-70°C, more preferably 55-65°C, and more preferably 60°C; the vacuum drying time is preferably 10-14h, more preferably 11-13h, and more preferably 11.5-12h.

[0068] In the present invention, the preparation method of the Ag NPs in step (2) and the Ag NPs in step (b) preferably comprises the following steps:

[0069] Silver nitrate, water, and sodium citrate solution were mixed and reacted, and then a sample obtained by the reaction was mixed with ethanol to obtain Ag NPs.

[0070] In the present invention, the mass fraction of the sodium citrate solution is preferably 0.5-1.5%, more preferably 0.7-1.3%, and more preferably 1-1.1%; the mass volume ratio of silver nitrate, water and sodium citrate solution is preferably 30-40 mg: 180-220 mL: 3-5 mL, more preferably 32-38 mg: 190-210 mL: 3.5-4.5 mL, and more preferably 35-36 mg: 200-205 mL: 4-4.2 mL.

[0071] In the present invention, silver nitrate, water and sodium citrate solution are mixed, and the reaction preferably comprises the following steps: mixing silver nitrate and water, heating to reflux, preferably for 5 to 15 minutes, more preferably for 7 to 13 minutes, and more preferably for 10 to 12 minutes; then quickly adding sodium citrate solution, and continuing to reflux, preferably for 0.5 to 1.5 hours, more preferably for 0.7 to 1.3 hours, and more preferably for 1 to 1.1 hours.

[0072] In the present invention, the sample obtained by the reaction is naturally cooled to room temperature to obtain Ag NPs.

[0073] In the present invention, the solvent of the Ag NPs solution in step (2) and the Ag NPs solution in step (b) is preferably water, and the mass fraction of the Ag NPs solution in step (2) and the mass fraction of the Ag NPs solution in step (b) are independently preferably 0.01 to 0.1%, more preferably 0.02 to 0.08%, and more preferably 0.05 to 0.06%.

[0074] In the present invention, the mass volume ratio of the modified Co / C and Ag NPs solution in step (2) is preferably 25-35 mg: 180-220 mL, more preferably 27-33 mg: 190-210 mL, and more preferably 28-30 mg: 195-200 mL; the mass volume ratio of the modified Co / C / g-C3N4 and Ag NPs solution in step (b) is preferably 25-35 mg: 180-220 mL, more preferably 27-33 mg: 190-210 mL, and more preferably 28-30 mg: 195-200 mL.

[0075] In the present invention, the mixing in step (2) and the mixing in step (b) are carried out under stirring, and the temperature of the mixing in step (2) and the temperature of the mixing in step (b) are independently preferably 20 to 30°C, more preferably 22 to 28°C, and more preferably 25 to 26°C; the time of the mixing in step (2) and the time of the mixing in step (b) are independently preferably 25 to 35 min, more preferably 27 to 33 min, and more preferably 28 to 30 min.

[0076] In the present invention, after the mixing in step (2) or step (b) is completed, the sample is collected by a magnet, and the collected sample is washed with ethanol, and the number of washings is preferably ≥1 time, more preferably ≥2 times, and more preferably ≥3 times; after the washing, vacuum drying is performed, and the vacuum drying temperature is preferably 50 to 70°C, more preferably 55 to 65°C, and more preferably 60 to 62°C; the vacuum drying time is preferably 10 to 14 hours, more preferably 11 to 13 hours, and more preferably 11.5 to 12 hours.

[0077] In the present invention, the preparation method of g-C3N4 in step (3) preferably comprises the following steps:

[0078] Melamine is subjected to a first calcination and a second calcination in sequence, and then the sample obtained by the second calcination is mixed with methanol and subjected to ultrasonic treatment to obtain g-C3N4.

[0079] In the present invention, the temperature of the first calcination is preferably 500-600°C, more preferably 520-580°C, and more preferably 550-560°C; the time of the first calcination is preferably 3-5h, more preferably 3.5-4.5h, and more preferably 3.9-4h; the temperature of the second calcination is preferably 500-600°C, more preferably 520-580°C, and more preferably 550-560°C; the time of the second calcination is preferably 1-3h, more preferably 1.5-2.5h, and more preferably 1.9-2h.

[0080] In the present invention, the mass volume ratio of the sample obtained by the second calcination to methanol is preferably 0.05-0.15 g: 3-7 mL, more preferably 0.07-0.13 g: 4-6 mL, and more preferably 0.1 g: 5 mL; the time for ultrasonic treatment is preferably 100-140 min, more preferably 110-130 min, and more preferably 120-125 min.

[0081] In the present invention, the mass ratio of Co / C / Ag and g-C3N4 in step (3) is preferably 25-35 mg: 25-35 mg, more preferably 27-33 mg: 27-33 mg, and more preferably 28-30 mg: 28-30 mg.

[0082] In the present invention, the incubation in step (3) is carried out under stirring, and the incubation temperature is preferably 20-30°C, more preferably 22-28°C, and more preferably 25-26°C; the incubation time is preferably 25-35 min, more preferably 27-33 min, and more preferably 28-30 min.

[0083] In the present invention, after the incubation in step (3) is completed, the sample is collected using a magnet, and the collected sample is washed with ethanol, and the number of washes is preferably ≥1 time, more preferably ≥2 times, and more preferably ≥3 times; vacuum drying is performed after the washing, and the vacuum drying temperature is preferably 50-70°C, more preferably 55-65°C, and more preferably 60-62°C; the vacuum drying time is preferably 10-14h, more preferably 11-13h, and more preferably 11.5-12h.

[0084] The present invention also provides a magnetic ternary composite photocatalytically degradable and recyclable SERS substrate prepared by the preparation method of the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate.

[0085] The present invention also provides application of the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate in surface enhanced Raman scattering.

[0086] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0087] Example 1

[0088] 0.014 mol of cobalt nitrate hexahydrate and 400 mL of methanol were mixed to obtain solution a; 0.064 mol of 2-methylimidazole and 400 mL of methanol were mixed to obtain solution b; solution b was quickly poured into solution a, stirred for 10 min, and allowed to stand for aging at 25°C for 24 h. After the aging treatment, it was centrifuged to obtain a purple solid; the purple solid was washed 3 times with methanol, transferred to a 60°C oven for drying for 24 h, and a zeolite imidazole framework (ZIF-67) was obtained; ZIF-67 was calcined at 150°C for 2 h in a nitrogen atmosphere, and then heated to 800°C at a heating rate of 5°C / min, calcined for 6 h, and after the calcination, naturally cooled to room temperature to obtain Co / C;

[0089] Co / C was vacuum dried at 60°C for 5 h, and then 1.0 g of the dried Co / C, 1.5 mL of (3-aminopropyl)triethoxysilane and 40 mL of toluene were mixed and modified at 110°C for 24 h. After the modification, the obtained sample was washed with ethanol for 3 times, and then vacuum dried at 60°C for 12 h to obtain modified Co / C;

[0090] 34 mg of silver nitrate and 200 mL of water were mixed and heated to reflux for 10 min; then 4 mL of 1% sodium citrate solution was quickly added and refluxed for 1 h to complete the reaction. The sample obtained by the reaction was naturally cooled to room temperature to obtain AgNPs;

[0091] 30 mg of modified Co / C was suspended in 200 mL Ag NPs solution (the solvent of the Ag NPs solution was water, and the mass fraction of the Ag NPs solution was 0.03%), and stirred at 25°C for 30 min. After the suspension, the sample was collected using a magnet, and the collected sample was washed three times with ethanol and dried in vacuum at 60°C for 12 h to obtain Co / C / Ag.

[0092] Melamine was calcined at 550°C for 4 hours to obtain a block sample, which was then calcined at 550°C for 2 hours. After calcination, it was mixed with methanol (the mass volume ratio of the sample obtained by the second calcination to methanol was 0.1 g: 5 mL), and ultrasonically treated for 120 minutes to obtain a thin g-C3N4 sheet (denoted as g-C3N4);

[0093] 30 mg Co / C / Ag and 30 mg g-C3N4 were mixed, incubated with stirring at 25°C for 30 min, collected using a magnet, and the collected samples were washed three times with ethanol and vacuum dried at 60°C for 12 h to obtain a magnetic ternary composite photocatalytic degradation and recovery SERS substrate (labeled as Co / C / Ag / g-C3N4).

[0094] The magnetic ternary composite photocatalytically degradable and recyclable SERS substrate prepared in this embodiment was subjected to SEM characterization and TEM characterization to obtain a SEM characterization image of the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate in this embodiment, as shown in FIG. Figure 1 As shown; TEM characterization of the magnetic ternary composite photocatalytic degradation and recovery SERS substrate in this embodiment, as shown Figure 2 As shown. Figure 1 and 2 It can be seen that Co / C / Ag is uniformly distributed on the ultrathin g-C3N4 nanosheets, and many cavity defects are formed in g-C3N4 during the secondary calcination and ultrasonication process.

[0095] The magnetic ternary composite photocatalytic degradation and recovery SERS substrate prepared in this embodiment was used to -8 The malachite green solution of M was subjected to SERS detection to obtain the SERS spectrum of the malachite green solution of the magnetic ternary composite photocatalytic degradation and recovery SERS substrate in this embodiment, as shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the substrate has a strong enhanced Raman signal response.

[0096] The magnetic ternary composite photocatalytic degradation and recovery SERS substrate prepared in this example was used to detect malachite green residues in aquaculture water, and Raman spectra and linear relationship diagrams at different malachite green concentrations were obtained, as shown in FIG. Figure 4 As shown; Figure 4 In the figure, A is the Raman spectra of different malachite green concentrations, and B is the corresponding 1613cm -1 Linear relationship diagram of intensity at wave number, 10000 means signal intensity scale. Figure 4 It can be seen that at concentrations as low as 10 -10 M, the characteristic bands can still be distinguished, which is better than most reported materials; 1613cm -1 The logarithmic linear equation of the intensity and the corresponding concentration is Y = (93573.1 ± 2063.9) + (9230.8 ± 207.2) X, and the correlation coefficient (R 2 ) was calculated to be 0.998, and the detection limit (LOD) was 8.2×10 -11 M.

[0097] The recovery performance of the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate prepared in this example was tested. Specifically, 10 mg of the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate prepared in this example was placed in 1 mL of a 10 -5 M malachite green solution, exposed to visible light for 120min to ensure complete degradation of malachite green. Then magnetic separation was performed, and the substrate was repeatedly rinsed with distilled water to remove residual inorganic small molecules or ions. After the first cycle, the recovered substrate was vacuum dried before the subsequent SERS detection and degradation. The above process was repeated 4 times to obtain a schematic diagram of the recovery performance of the magnetic ternary composite photocatalytic degradation and recovery SERS substrate in this embodiment, as shown in FIG. Figure 5 As shown. Figure 5 It can be seen that no obvious SERS signal was found on the magnetic ternary composite photocatalytic degradation and recovery SERS substrate obtained at the end of the cycle. The last repeated detection was 1613 cm -1 The peak intensity at 40° decreased to 80.6% of the initial value, which may be due to the decrease in the adsorption capacity of the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate. The above results prove that the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate can be successfully recycled and can be used as a promising recyclable SERS substrate for practical detection.

[0098] Example 2

[0099] Melamine was calcined at 550°C for 4 hours to obtain a block sample, which was then calcined at 550°C for 2 hours. After calcination, it was mixed with methanol (the mass volume ratio of the sample obtained by the second calcination to methanol was 0.1 g: 5 mL), and ultrasonically treated for 120 minutes to obtain a thin g-C3N4 sheet (denoted as g-C3N4);

[0100] 0.014 mol of cobalt nitrate hexahydrate and 400 mL of methanol were mixed to obtain solution a; 0.064 mol of 2-methylimidazole and 400 mL of methanol were mixed to obtain solution b; 1.0 g of g-C3N4 was added to solution a, stirred for 10 min, and then solution b was quickly poured into solution a containing g-C3N4, stirred for 10 min, and allowed to stand for aging at 25°C for 24 h. After the aging treatment, centrifugation was performed to obtain a purple solid; the purple solid was washed 3 times with methanol, transferred to a 60°C oven for drying for 24 h, and a composite framework (ZIF-67 / g-C3N4) was obtained; in a nitrogen atmosphere, ZIF-67 / g-C3N4 was calcined at 150°C for 2 h, and then heated to 500°C at a heating rate of 5°C / min, calcined for 6 h, and after the calcination, naturally cooled to room temperature to obtain Co / C / g-C3N4;

[0101] Co / C / g-C3N4 was vacuum dried at 60°C for 5 h, and then 1.0 g of the dried Co / C, 1.5 mL of (3-aminopropyl)triethoxysilane and 40 mL of toluene were mixed and modified at 110°C for 24 h. After the modification, the obtained sample was washed with ethanol for 3 times and then vacuum dried at 60°C for 12 h to obtain modified Co / C / g-C3N4;

[0102] 34 mg of silver nitrate and 200 mL of water were mixed and heated to reflux for 10 min; then 4 mL of 1% sodium citrate solution was quickly added and refluxed for 1 h to complete the reaction. The sample obtained by the reaction was naturally cooled to room temperature to obtain AgNPs;

[0103] 30 mg of modified Co / C / g-C3N4 was suspended in 200 mL of Ag NPs solution (the solvent of the Ag NPs solution was water, and the mass fraction of the Ag NPs solution was 0.03%), stirred at 25°C for 30 min, and then collected using a magnet. The collected samples were washed three times with ethanol and vacuum dried at 60°C for 12 h to obtain a magnetic ternary composite photocatalytic degradation and recovery SERS substrate (marked as Co / C / g-C3N4 / Ag).

[0104] It can be seen from the above embodiments that the present invention provides a method for preparing a magnetic ternary composite photocatalytically degradable and recyclable SERS substrate, comprising the following steps: mixing Co / C, (3-aminopropyl) triethoxysilane and toluene, performing a modification treatment to obtain modified Co / C; mixing the modified Co / C and Ag NPs solution to obtain Co / C / Ag; mixing Co / C / Ag and g-C3N4, incubating to obtain a magnetic ternary composite photocatalytically degradable and recyclable SERS substrate (Co / C / Ag / g-C3N4); or, mixing Co / C / g-C3N4, (3-aminopropyl) triethoxysilane and toluene, performing a modification treatment to obtain modified Co / C / g-C3N4; mixing the modified Co / C / g-C3N4 and Ag NPs solution to obtain a magnetic ternary composite photocatalytically degradable and recyclable SERS substrate (Co / C / g-C3N4 / Ag). The present invention designs and prepares a Co / C / Ag / g-C3N4 substrate and a Co / C / g-C3N4 / Ag substrate. The three components are combined and synergistic to achieve a very excellent visible light catalytic effect.

[0105] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a magnetic ternary composite photocatalytically degradable and recyclable SERS substrate, characterized in that: It includes the following steps: (1) Co / C, (3-aminopropyl)triethoxysilane and toluene are mixed and modified to obtain modified Co / C; (2) mixing the modified Co / C and Ag NPs solutions to obtain Co / C / Ag; (3) mixing Co / C / Ag and g-C3N4 and incubating them to obtain the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate; Alternatively, (a) Co / C / g-C3N4, (3-aminopropyl)triethoxysilane and toluene are mixed and modified to obtain modified Co / C / g-C3N4; (b) The modified Co / C / g-C3N4 and AgNPs solution are mixed to obtain the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate.

2. The method for preparing the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate according to claim 1, characterized in that: The preparation method of Co / C in step (1) comprises the following steps: Cobalt nitrate, 2-methylimidazole and methanol are mixed and aged to obtain a zeolite imidazole framework; the zeolite imidazole framework is subjected to a first calcination and a second calcination in sequence under a protective atmosphere to obtain Co / C; The preparation method of Co / C / g-C3N4 in step (a) comprises the following steps: (I) melamine is subjected to a first calcination and a second calcination in sequence, and then a sample obtained by the second calcination is mixed with methanol and subjected to ultrasonic treatment to obtain g-C3N4; (II) Cobalt nitrate, 2-methylimidazole, methanol and g-C3N4 are mixed and aged to obtain a composite framework; under a protective atmosphere, the composite framework is subjected to a first calcination and a second calcination in sequence to obtain Co / C / g-C3N4.

3. The method for preparing the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate according to claim 1 or 2, characterized in that: The mass volume ratio of Co / C, (3-aminopropyl)triethoxysilane and toluene in step (1) is 0.1-1 g: 1-2 mL: 35-60 mL; The mass volume ratio of Co / C / g-C3N4, (3-aminopropyl)triethoxysilane and toluene in step (a) is 0.1-1 g: 1-2 mL: 35-60 mL.

4. The method for preparing the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate according to claim 3, characterized in that: The temperature of the modification treatment in step (1) and the temperature of the modification treatment in step (a) are independently 100 to 120° C., and the time of the modification treatment in step (1) and the time of the modification treatment in step (a) are independently 22 to 26 hours.

5. The method for preparing the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate according to claim 4, characterized in that: The preparation method of the Ag NPs in step (2) and the Ag NPs in step (b) comprises the following steps: Silver nitrate, water and sodium citrate solution are mixed and reacted to obtain AgNPs.

6. The method for preparing the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate according to claim 1 or 5, characterized in that: The solvent of the Ag NPs solution in step (2) and the Ag NPs solution in step (b) is water, and the mass fraction of the Ag NPs solution in step (2) and the mass fraction of the Ag NPs solution in step (b) are independently 0.01 to 0.1%; The mass volume ratio of the modified Co / C and Ag NPs solution in step (2) is 25-35 mg: 180-220 mL; the mass volume ratio of the modified Co / C / g-C3N4 and Ag NPs solution in step (b) is 25-35 mg: 180-220 mL; The mixing temperature in step (2) and the mixing temperature in step (b) are independently 20 to 30° C., and the mixing time in step (2) and the mixing time in step (b) are independently 25 to 35 minutes.

7. The method for preparing the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate according to claim 6, characterized in that: The preparation method of g-C3N4 in step (3) comprises the following steps: Melamine is subjected to a first calcination and a second calcination in sequence, and then the sample obtained by the second calcination is mixed with methanol and subjected to ultrasonic treatment to obtain g-C3N4.

8. The method for preparing the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate according to claim 7, characterized in that: The mass ratio of Co / C / Ag and g-C3N4 in step (3) is 25-35 mg: 5-35 mg; The incubation temperature in step (3) is 20-30° C., and the incubation time is 25-35 min.

9. A magnetic ternary composite photocatalytically degradable and recyclable SERS substrate prepared by the method for preparing a magnetic ternary composite photocatalytically degradable and recyclable SERS substrate as claimed in any one of claims 1 to 8.

10. Use of the magnetic ternary composite photocatalytically degradable and recyclable SERS substrate according to claim 9 in surface enhanced Raman scattering.